Development of national qualification system based on education sphere and labour market interface - Gazaliyev, Arstan; Pak, Yuri (Nazarbayev University Graduate School of Education, 2015)
This paper discusses issues of developing national and branch frameworks of qualifications. It provides ways of overcoming the existing gap between requirements of the labour market and employee’s competences. It also provides a definition of the national system of qualifications and the branch system of qualifications and labour functions. It also offers requirements to developing professional standards and shows their importance for forming a university graduate’s competence-based model. A professional standard should be considered as the backbone document for the development of educational programmes aimed at the formation of the key competences providing the demand for graduates in the labour market throughout the life.
Keywords: Eurasian Higher Education Leaders’ Forum; development of national qualification system; education sphere; labour market interface; frameworks; knowledge; abilities and skills; personal and professional competences